Monetary policy and financial stability: Should central bank lean against the wind? - Aswathi R. Nair; B. Anand (Central Bank Review (CBR), 2020)
After the global financial crisis, it was observed that price stability alone would not ensure financial stability. The new paradigm indeed insists on the inclusion of financial stability as an additional macroeconomic objective. In this context, it is essential to understand how exactly is the new objective of financial stability will be placed in the existing framework. Also, the efficacy of monetary policy in this regard needs to be thoroughly discussed. This paper probes into the employability of monetary policy as a tool to achieve financial stability. We, therefore, compare between interest rates obtained from the standard Taylor rule and asset price augmented Taylor rule in the Indian context. The results suggest that targeting asset prices can be one of the effective ways to contain financial instabilities and consequent economic slumps.
Keywords: B23; E44; E52; P44; 330; Taylor rule; Monetary policy; Financial stability; Generalised method of moments